Ulcerative colitis: management in adults, children and young people – concise guidance - Tun, Gloria SZ (Clin Med (Lond), 2017)
Ulcerative colitis is a chronic, relapsing and remitting inflammatory disease of the colon and rectum. Effective management requires prompt recognition and treatment of those with acute relapses as well as appropriate choice and monitoring of drugs for maintenance of remission. This therefore involves specialist gastroenterology teams as well as acute and general physicians and primary care clinicians. Treatment options need to be discussed with those with ulcerative colitis and their families and appropriate information provided. This concise guideline focuses (with the generalist particularly in mind) on recommendations from the National Institute for Health and Care Excellence clinical guideline 166 considered of key importance for implementation.